Mối quan hệ phi tuyến tính giữa bất định chính sách kinh tế và cạnh tranh ngân hàng - Lê Huỳnh , Như (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study investigates the impact of economic policy uncertainty on banking competitiveness by analyzing data from 1.006 banks in 20 countries worldwide sourced from Refinitiv Eikon during the period 2009‒2023. Employing fixed effects, feasible generalized least squares, Driscoll-Kraay standard errors, and IV-GMM for panel data, the findings reveal a positive influence of economic policy uncertainty on banking sector competitiveness, as measured by both the economic policy uncertainty index and the World Uncertainty Index. However, nonlinear effects are only evident in the case of the economic policy uncertainty index. Furthermore, when examining developing and developed countries separately, the economic policy uncertainty index exhibits an inverted U-shaped relationship with banking sector competitiveness in developed countries and a U-shaped relationship in developing countries. For the World Uncertainty Index, only an inverted U-shaped relationship is found in developing countries. Consequently, this study proposes several policy implications to assist bank managers in formulating appropriate strategies to both navigate the challenges posed by the economic policy uncertainty environment and enhance their competitive edge.